PANDANGAN KE AGAMAAN GERE JA ELIM TEBERNAKEL - Abdul Kadir R (Al-Qalam, 2008)
This study was conducted at Ambon. This aims to describe the religiousperspective of Elim Tebernakel Church. Data was collected using interviewand observation. Then, data was analyzed using qualitative description.This study indicates that (1) Elim Tebernakel rejects the liberal interpretationto the Holy Bible. Holy Bible is always true in everlasting time; (2)respects to faith differention between different religion; (3) denies integrationbetween local culture and religion; (4) rejects religion-state